Dinamika Pembangunan Gorong-Gorong Terhadap Lalu Lintas di Jalan Ketintang Surabaya - Farukh, Ahmada (Universitas Merdeka Madiun, 2024)
The construction of culverts carried out on Jalan Ketintang, resulted in a significant impact on the surrounding environment. Street vendors who sell around the construction project and road users who pass by are the ones who feel the most impact. This research was conducted to find out how the dynamics that occur in the community around the construction site, especially for street vendors and road users along Jalan Ketintang. This research is qualitative and carried out with a phenomenological approach. The theory used as the basis of this research is the theory of social change proposed by Emile Durkheim. From this research, it is known that the street vendors who were affected by the construction of culverts were relocated to the newly built culinary center. However, the impact on road users seems to have been neglected, so there are many materials that hinder road users and often result in traffic jams.